Adat dan Syariat : Manifestasi Islam dalam Perkawinan Lampung Pepadun - Huzaini Huzaini; Rachmat Panca Putera (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The Lampung Pepadun wedding tradition represents a harmony between local culture and Islamic values. This study aims to identify the manifestation of Islamic principles within the Lampung Pepadun wedding tradition and explain the alignment between local customs and Islamic law in its practice. Using a phenomenological qualitative approach, data were collected through in-depth interviews with cultural and religious leaders, direct observations of wedding ceremonies, and document analysis. The findings reveal that this tradition systematically integrates elements of Islamic law, such as the marriage contract (akad), dowry (mahar), and communal prayers, without eliminating the unique symbols and cultural meanings of the local practices. The study also highlights the significant role of religious figures in preserving Islamic values amid the challenges of modernization, which often influence the implementation of traditions. These findings suggest that local traditions grounded in religious values have significant potential to serve as a medium for cultural preservation and spiritual reinforcement within communities. Therefore, preserving such traditions through approaches consistent with Islamic law is essential to maintaining cultural identity and community religiosity.